Charge mobility enhancement for diketopyrrolopyrrole-based conjugated polymers by partial replacement of branching alkyl chains with linear ones. (19th September 2017) - Ma, Jing; Liu, Zitong; Wang, Zhijie; Yang, Yizhou; Zhang, Guanxin; Zhang, Xisha; Zhang, Deqing
Abstract : Side-chain engineering of three new conjugated D–A terpolymers by varying the number of branching and linear alkyl chains is presented for OFET studies. Abstract : Conjugated D–A polymers with high charge mobilities have received increasing attention in recent years. In this paper, we report a simple, but efficient approach to improve the charge mobilities of conjugated polymers by partial replacement of branching alkyl chains with linear ones. With this strategy in mind, we designed and investigated three new DPP-quaterthiophene terpolymersPDPP4T-1, PDPP4T-2 andPDPP4T-3 containing both linear ( n -dodecane) and branching (2-decyltetradecyl) alkyl chains with different ratios. On the basis of GIWAXS data, interchain packing order is improved for terpolymersPDPP4T-1, PDPP4T-2 andPDPP4T-3, in comparison withPDPP4T with only branching alkyl chains. The incorporation of linear alkyl chains can affect the interchain packing mode, andPDPP4T-3 with more linear alkyl chains among the three terpolymers adopts the edge-on chain arrangement on the substrate. Field effect transistor measurements indicate thatPDPP4T-1, PDPP4T-2 andPDPP4T-3 exhibit higher hole mobilities thanPDPP4T . Moreover, the hole mobilities increase in the following order:PDPP4T-1 <PDPP4T-2 <PDPP4T-3 by increasing the content of linear alkyl chains in these terpolymers. The thin film mobility ofPDPP4T-3 can reach 6.1 cm 2 V −1 s −1, which can be further increased to 9.1 cm 2 V −1 s −1 after incorporatingNMe4 I .